Enhancing Anti-Allergic Transdermal Patches Through Box-Behnken Design Approach with Chlorpheniramine Maleate: Pharmaceutical sciences- Pharmaceutics - Abdul Ahad, Hindustan; Dheeraj, Siriguppa; Chinthaginjala, Haranath (International Journal of Life Science and Pharma Research, 2023)
This research focuses on developing transdermal patches incorporating chlorpheniramine maleate (CPM), an anti-allergic medication. Transdermal patches offer a convenient and effective way to administer drugs, and CPM's application in this context holds promise for improved patient care. The primary aim of this study was to utilize the Box-Behnken design to formulate transdermal patches containing CPM. These patches were developed through a solvent dispersion technique, with key ingredients including HPMC (a polymer), PEG (a plasticizer), ethanol, and a permeation enhancer. The overarching goal was to assess the impact of polymer type, permeation enhancer, and sonication time on patch formulation and performance. To achieve our aim, we conducted several tests, including folding endurance, drug content, thickness, entrapment efficiency, in vitro moisture uptake, permeation analysis, and in vitro experiments. These specific objectives allowed us to evaluate the quality and effectiveness of the transdermal patches comprehensively. In our methodology, HPMC was employed as the polymer, and PEG served as the plasticizer. The Box-Behnken design facilitated kinetic assessments to study drug release from the patches. We systematically varied the HPMC, PEG, and ethanol concentrations and the sonication time to optimize patch formulation. The outcomes of our study indicated that all formulated patches met the specified criteria for quality and performance. Folding endurance was found to follow the formula +178.00 + 5.37A + 13.25B + 1.13C - 1.75AB + 0.0000AC + 0.2500BC + 4.25A² + 8.50B² + 2.75C², while permeation at 24 hours exhibited the equation +73.00 + 2.12A + 6.37B + 0.7500C - 0.5000AB - 0.2500AC - 0.2500BC + 1.00A² + 0.0000B² + 1.25C². These findings underscore the successful development of transdermal patches containing CPM and shed light on the critical factors influencing patch formulation. In summary, this investigation accomplished the development of transdermal patches incorporating CPM and elucidated the influence of polymer type, permeation enhancer, and sonication time on the formulation process. These findings contribute to advancing transdermal drug delivery systems and offer potential benefits for patients receiving anti-allergic medication.